2005
DOI: 10.1074/jbc.m506996200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of WASP by the Cdc42-associated Kinase ACK1

Abstract: ACK1 is a nonreceptor tyrosine kinase that associates specifically with Cdc42. Relatively few ACK1 substrates and interacting proteins have been identified. In this study, we demonstrated that ACK1 phosphorylates the Wiskott-Aldrich syndrome protein (WASP), a Cdc42 effector that plays an important role in the formation of new actin filaments. ACK1 and WASP interact in intact cells, and overexpression of ACK1 promotes WASP phosphorylation. Phosphorylation of WASP in vitro was enhanced by the addition of Cdc42 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 45 publications
1
35
0
Order By: Relevance
“…Phosphorylation of N-WASP/WASP proteins by non-receptor tyrosine kinases, such as ACK1 enhances the ability of WASP to stimulate actin polymerization (22), whereas growth factor stimulation of cultured cells results in hyper-phosphorylation of the WAVE proteins as well as a delay in their mobility in SDS-PAGE (23). WAVE1 was shown to be phosphorylated by the cyclindependent kinase 5 (24), whereas phosphorylation of WAVE2 has recently been shown to involve the non-receptor tyrosine kinase c-Abl (25), resulting in both cases in the stimulation of membrane ruffling and cell spreading.…”
mentioning
confidence: 99%
“…Phosphorylation of N-WASP/WASP proteins by non-receptor tyrosine kinases, such as ACK1 enhances the ability of WASP to stimulate actin polymerization (22), whereas growth factor stimulation of cultured cells results in hyper-phosphorylation of the WAVE proteins as well as a delay in their mobility in SDS-PAGE (23). WAVE1 was shown to be phosphorylated by the cyclindependent kinase 5 (24), whereas phosphorylation of WAVE2 has recently been shown to involve the non-receptor tyrosine kinase c-Abl (25), resulting in both cases in the stimulation of membrane ruffling and cell spreading.…”
mentioning
confidence: 99%
“…The actin nucleation promoting activity of WASP is increased by phosphorylation at Y256, Y291, S242, S483 and S484 sites of WASP (Cory et al, 2002, 2003; Yokoyama et al, 2005), which stabilizes its open active conformation. We have shown that BCR activation increases the levels of phosphorylated WASP and recruits phosphorylated WASP to the membrane of B cells at the contact zone in a Btk-dependent manner (Sharma et al, 2009; Liu et al, 2011).…”
Section: Bcr Signaling Initiates and Regulates Actin Reorganizationmentioning
confidence: 99%
“…However, whether Btk can directly phosphorylate WASP is not known. It has been suggested that WASP is a substrate of the Src family kinase Hck (Cory et al, 2002) and activated Cdc42-associated kinase 1 (ACK1) (Yokoyama et al, 2005), but whether these kinases are responsible for WASP phosphorylation in B cells and their relationship with Btk have not yet been determined. The actin binding ability of ezrin is controlled by phosphorylation at T567 (Table 1).…”
Section: Bcr Signaling Initiates and Regulates Actin Reorganizationmentioning
confidence: 99%
“…The non-receptor tyrosine kinase ACK1 phosphorylates and enhances the WASP-mediated actin polymerization [70], while stimulation of cultured cells with growth factors increases the phosphorylation levels of the WAVE proteins [71]. Phosphorylation of WAVE1 by CDK5 [72], or of WAVE2 by the non-receptor tyrosine kinase c-Abl [73], leads to the stimulation of membrane ruffling and cell spreading [74].…”
Section: Mechanisms Of Regulation Of Wave3mentioning
confidence: 99%